Electron-free nuclear matter: magnetic confinement and binding of bare nuclei in extreme fields - Barack Ndenga (My University, 2025)
We propose a theoretical framework for a new state of matter—Electronless Nuclear Matter (ENM)—where bare atomic nuclei are stably confined and bonded through structured magnetic fields, without the involvement of electrons. We formulate five fundamental laws governing the organization, stability, and bonding of such nuclei in high-intensity magnetic traps. A modified Schrödinger equation is introduced to describe the quantum behavior of bare nuclei under magnetic confinement, and a new class of magnetic potential wells is proposed as the organizing principle of nuclear lattices. We predict the emergence of nuclear crystals, exotic magnetic phases, and resonance modes unique to this electronless regime. This paradigm opens the possibility of a magneto-nuclear periodic table, redefines the concept of chemical bonding, and suggests the existence of matter in forms previously considered impossible. The framework has potential implications in astrophysical environments such as magnetars, as well as in ultrahigh-field laboratory experiments. This work invites experimentalists and theorists to explore post-electronic architectures of matter governed purely by nuclear and magnetic interactions.